Always look on the bright side of life a sortabiography - Idle, Eric 1943- (Weidenfeld & Nicolson, an imprint of The Orion Publishing Group Ltd, 2018)
"We know him best for his unforgettable roles on Monty Python - from the Flying Circus to The Meaning of Life. Now, Eric Idle reflects on the meaning of his own life in this entertaining memoir that takes us on a remarkable journey from his childhood in an austere boarding school through his successful career in comedy, television, theatre and film. Coming of age as a writer and comedian during the Sixties and Seventies, Eric stumbled into the crossroads of the cultural revolution and found himself rubbing shoulders with the likes of George Harrison, David Bowie and Robin Williams, all of whom became lifelong friends. With anecdotes sprinkled throughout involving Mike Nichols, Mick Jagger, Steve Martin, Paul Simon and many more, as well as the Pythons themselves, Eric captures a time of tremendous creative output with equal parts hilarity and heart. In Always Look on the Bright Side of Life, named after the song he wrote for Life of Brian which has since become the number-one song played at funerals in the UK, he shares the highlights of his life and career with the kind of offbeat humour that has delighted his audiences for five decades."--Publisher's description
Includes index
Keywords: Idle, Eric -- 1943-; Idle, Eric; Monty Python (Comedy troupe); Comedians / Great Britain / Biography; Motion picture actors and actresses / Great Britain / Biography; Comedians; Motion picture actors and actresses; Great Britain; Autobiographies; Biography; Autobiografie